2018
DOI: 10.1002/cyto.b.21622
|View full text |Cite
|
Sign up to set email alerts
|

A standardized flow cytometry procedure for the monitoring of regulatory T cells in clinical trials

Abstract: Our results highlight the reliability of this high-standard protocol that could become a reference method for the monitoring of Tregs in clinical trials. © 2018 International Clinical Cytometry Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…Later on, the role of these cells in sepsis‐induced innate and adaptive alterations was showed . Thanks to the improvement in flow cytometry phenotyping such as the addition of CD127 staining and standardization of intracellular Foxp3 staining for its use in clinic , large prospective multicenter clinical studies have evaluated this parameter in ICU patients . It was showed that increased percentage of Treg in critically ill patients is associated with increased risk of subsequent nosocomial infections and that this parameter could be part of an immunopanel to stratify patients suitable for immuno‐intervention in a precision medicine approach .…”
Section: Landmarks Of Flow Cytometry In Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…Later on, the role of these cells in sepsis‐induced innate and adaptive alterations was showed . Thanks to the improvement in flow cytometry phenotyping such as the addition of CD127 staining and standardization of intracellular Foxp3 staining for its use in clinic , large prospective multicenter clinical studies have evaluated this parameter in ICU patients . It was showed that increased percentage of Treg in critically ill patients is associated with increased risk of subsequent nosocomial infections and that this parameter could be part of an immunopanel to stratify patients suitable for immuno‐intervention in a precision medicine approach .…”
Section: Landmarks Of Flow Cytometry In Sepsismentioning
confidence: 99%
“…In addition, the development of lyophilized pre‐formulated antibody panels also represents a major improvement for FCM standardization in RCTs. As an example, FOXP3‐lyophilized tubes are currently used for regulatory T cells determination in an RCT evaluating low‐dose IL‐2 treatment for type 1 diabetes (DIABIL‐2 study, NCT02411253). Furthermore, new technical developments (low cost compact portable flow cytometer, bedside flow cytometry or chip‐based flow cytometry) are now being proposed that will facilitate the use of Flow at the bedside in ICU (see above in mHLA‐DR paragraph ).…”
Section: Current Multicenter Studies and Clinical Trialsmentioning
confidence: 99%
“…Similar dried antibody mixtures have already proven to yield high-data reproducibility and reliability in large-scale projects such as the ONE study [13], the PreciseADS study [34], and others [35][36][37]. These reagents contain exactly the same amount of dried antibodies precoated in individual tubes for direct labelling of cells from the same batch and are very stable overtime, offering the advantage of speeding up and simplifying the labelling procedure, reducing the number of technical steps, and avoiding the maximum of biases.…”
mentioning
confidence: 99%
“…In our studies, we have used whole peripheral blood as the starting sample which has been the routine over the years in this cytometry laboratory, instead of isolated mononuclear cells via Ficoll discontinuous gradient centrifugation (Böyum, ). Two recent reports actually favor the whole blood approach, as it saves time and is equally reliable as the staining of isolated mononuclear cells (Jimenez Vera et al, ; Pitoiset et al, ). While our report is centered on utilizing a two‐laser, four‐fluorescent labels plus forward scattering‐side scattering approach for gating on lymphocytes and then on CD4‐T cells, it is possible to utilize instruments with more lasers and thus more fluorescent labels.…”
Section: Discussionmentioning
confidence: 99%